Screening to Detect Hip and Groin Problems in Elite Adolescent Football (Soccer) Players – Friend or Foe? - Matthew D DeLang; J. Craig Garrison; Kristian Thorborg (International Journal of Sports Physical Therapy)
Injury prevention strategies in team settings should not overlook early detection and secondary prevention. Monitoring systems may be an effective approach to detect common and troublesome injuries, such as hip and groin pain in football (soccer) players. The purpose of this International Perspective is to share our experiences with monitoring hip and groin pain in youth academy football and discuss challenges that surfaced. We consider why players may not accurately report pain, their perceptions of groin pain, and whether all groin pain is clinically meaningful.